Biomechanics applied to incisional hernia repair: considering the critical and the gained resistance towards impacts related to pressure - Kallinowski, Friedrich; Ludwig, Yannique; Löffler, T.; Vollmer, M.; Lösel, Philipp; Voß, S.; Görich, J.; Heuveline, Vincent; Nessel, R. (Clinical biomechanics, 2021)
Background - Incisional hernia repair is burdened with recurrence, pain and disability. The repair is usually carried out with a textile mesh fixed between the layers of the abdominal wall. - Methods - We developed a bench test with low cyclic loading. The test uses dynamic intermittent strain resembling coughs. We applied preoperative computed tomography of the abdomen at rest and during Valsalva's maneuver to the individual patient to analyze tissue elasticity. - Findings - The mesh, its placements and overlap, the type and distribution of fixation elements, the elasticity of the tissue of the individual and the closure of the abdominal defect-all aspects influence the reconstruction necessary. Each influence can be attributed to a relative numerical quantity which can be summed up into a characterizing value. The elasticity of the tissues within the abdominal wall of the individual patient can be assessed with low-dose computed tomography of the abdomen with Valsalva's maneuver. We established a procedure to integrate the results into a surgical concept. We demonstrate potential computer algorithms using non-rigid b-spline registration and artificial intelligence to further improve the evaluation process. - Interpretation - The bench test yields relative values for the characterization of hernia, mesh and fixation. It can be applied to patient care using established procedures. The clinical application in the first ninety-six patients shows no recurrences and reduced pain levels after one year. The concept has been spread to other surgical groups with the same results in another fifty patients. Future efforts will make the abdominal wall reconstruction more predictable.
Publikationsdatum online: 29 December 2020
Gesehen am 03.07.2021